The enemies of the People in Athens at the end of the Peloponnesian War: Euripides’ Orestes and the rifts among the aristocrats - Moerbeck, Guilherme (Revista Archai, 2025)
This article integrates theoretical concepts not typically associated with ancient history, including generation, elite theory, and the horizon of expectation. It examines how political tensions in ancient Athens are culturally expressed in theatre, focusing on Euripides’ Orestes. Through the lens of historical consciousness and memory, the study explores how historical meaning is attributed and how existential temporality influences the interpretation of the past and present. The paper addresses whether rhetorical positions defending antidemocratic policies can be discerned in theatrical performances, identifying threats to democratic governance and the political arenas where crucial decisions are made. By analyzing Euripides’ Orestes (lines 682-775), the article aims to uncover the city’s response to political crises during the Peloponnesian War.